Distance Estimation based on 802.11 RTS/CTS Mechanism for Indoor Localization - Bahillo, Alfonso; Fernández, Patricia; Prieto, Javier; Mazuelas, Santiago; Lorenzo, Rubén M.; Abril, Evaristo J. (IntechOpen, 2011)
None